Health effects of air pollution in Iceland. Respiratory health in volcanic environments - Carlsen, Hanne Krage, 1981- (2014)
Statement of collaboration This thesis and the work in it have been produced in collaboration between The University of Iceland and Umeå University. The thesis will be defended and issued at both institutions. Air pollution has adverse effects on human health. The respiratory system is the most exposed and short-term changes in air pollution levels have been associated with worsening of asthma symptoms and increased rates of heart attacks and stroke. Air pollution in cities due to traffic is the major concern, as many people are exposed. However, natural sources of air pollution such as natural dust storms and ash from volcanic eruptions can also compromise human health. Exposure to volcanic eruptions and other natural hazards can also threaten mental health. Air pollution has not been extensively studied in Iceland, in spite of the presence of several natural pollution sources and a sizeable car fleet in the capital area. The aim of this thesis was to determine if there was a measurable effect on health which could be attributed to air pollution in Iceland. This aim was pursued along two paths; time series studies using register data aimed to determine the short-term association between daily variation in air pollution and on one hand daily dispensing of anti-asthma medication or the daily number of emergency room visits and emergency admissions for cardiopulmonary causes and stroke. The other method was to investigate if exposure to the Eyjafjallajökull volcanic eruption was associated with adverse health outcomes, either at the end of the eruption, or 6 months later. In paper I time series regression was used to investigate the association between the daily number of individuals who were dispensed anti-asthma medication and levels of the air pollutants particle matter with an aerodynamic diameter less than 10 μm (PM10), nitrogen dioxide (NO2), ozone (O3), and hydrogen sulfide (H2S) during the preceding days. For the study period 2006-9, there were significant associations between the daily mean of PM10 and ...